(3cJGH GdJfHjg aj TQM eTcd CHjGJ GdMeGSIs - (3CHh GdaJM YKeGf Hf Lfis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3Ydi Hf YHOGdQGRb Hf eMeO GdLYaQi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CjGOjg hMSf GdYGbHI ddeJbjf hbO CLHJc CjOc Gddg Edi edJeSc ef Yed eG ai GdMeGSI ef EYQGH heG jMdb Hg ef ETJbGb Ch JUQja Ch YQhV s
(3BNQgG (B:s
(3fGUdjkG ai eYfi fGUd hde JMOK HGA GdEVGaI TjFkG ZjQ eG cGf hMPa EMOi jGi GdEVGaI HYO EdMGbg EjGgeG ddJhcjO eYfi GdUaI aHbi CQGai ceG JQi gPG BNQ eG NQL ef JaSjQ EYQGH GdMeGSI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs